2021
DOI: 10.3389/fphar.2021.669236
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Emergent Co-Morbidities and Survival in Patients With Metastatic Castration-Resistant Prostate Cancer Receiving Abiraterone or Enzalutamide

Abstract: Secondary hormone therapy, abiraterone and enzalutamide, has improved outcomes for metastatic castration-resistant prostate cancer (mCRPC) and prolonged patients’ lives significantly. Various studies have compared the cancer-related outcomes, adverse effects, and drug-induced comorbidities in patients with mCRPC who are treated with abiraterone or enzalutamide. However, few studies have explored associations between survival and comorbidities or comprehensive analyzed newly developed comorbidities during and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Two studies (not identified in the current review) determined that patients treated with abiraterone reported less fatigue and cognitive impairment and had more favorable PROs compared with enzalutamide in both real-world and clinical trial settings ( 95 , 123 ). However, a propensity score-matching study found that whilst there was no significant difference in the development of new comorbidities between the two agents, OS was better with enzalutamide; moreover, the overall Charlson Comorbidity Index score (and not its items) was a significant predictor of OS ( 124 ). There is increasing awareness that HRQoL is an important endpoint of value to both patients and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (not identified in the current review) determined that patients treated with abiraterone reported less fatigue and cognitive impairment and had more favorable PROs compared with enzalutamide in both real-world and clinical trial settings ( 95 , 123 ). However, a propensity score-matching study found that whilst there was no significant difference in the development of new comorbidities between the two agents, OS was better with enzalutamide; moreover, the overall Charlson Comorbidity Index score (and not its items) was a significant predictor of OS ( 124 ). There is increasing awareness that HRQoL is an important endpoint of value to both patients and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…The OS rate in the current study showed no significant difference between the two groups, similar to the trends found in other Taiwan studies ( 13 , 22 ). However, a retrospective study conducted using the NHIRD showed that abiraterone (53.7%) had a significantly higher overall mortality rate than enzalutamide (40.55%) ( 23 ). Otherwise, the current study’s results on survival time were more similar to those observed in clinical trials and cohort studies from other countries.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Enzalutamide has improved outcomes for metastatic castration‐resistant prostate cancer (mCRPC) and prolonged patients' lives significantly. 7 According to highlights of prescribing of Food and Drug Administration, In four placebo‐controlled trials (AFFIRM, PROSPER, PREVAIL, and ARCHES), the most common adverse reactions (≥10%) that occurred more frequently (≥2% over placebo) in the XTANDI‐treated patients were asthenia/fatigue, back pain, hot flush, constipation, arthralgia, decreased appetite, diarrhea, and hypertension. Adverse reactions of enzalutamide including seizure, posterior reversible encephalopathy syndrome (PRES), hypersensitivity, ischemic heart disease, falls and fractures are warned and required precaution.…”
Section: Introductionmentioning
confidence: 99%